THE EFFECT OF THIEF LABELING ON YOUTHS - Kasmanto Rinaldi; Juni Ardianto (Bajang Institute, 2022)
The purpose of this study was to determine the effect of labeling on youths in X Village, Tambang District. The research method used in this research is using qualitative research methods which aim to describe the actual situation of what is happening at the research location through collecting, identifying and analyzing data in order to obtain the answers to be achieved. In this study using the labeling theory (Howard S. Becker and Edwin Lemert) which explains how society reacts to someone's behavior that is considered deviant and then labeled by their social environment to give rise to various influences on the people they label. The conclusion of this study is the need for public awareness of their views on youth who will eventually become victims of the community itself and trigger negative impacts on these youths.